REPRESENTASI PATRIARKI PADA TOKOH UTAMA DALAM SERIAL GADIS KRETEK KAJIAN SEMIOTIKA JOHN FISKE - Zafira Ardhea Rista; Anisha Intan Prameswari; Vania Abigail Putri Andrias (Universitas 17 Agustus 1945 Surabaya, 2026)
Film series have developed so rapidly among the public. In addition to being entertaining, serial films have the power to change society, affecting everything from people's ways of thinking to their daily behavior. This study analyzes the representation of patriarchy in the main characters of the